Fabrication of floor cleaner using Wi-Fi module - Pugazhenthi, N; Venkata Sai Reddy, P; Akash Reddy, M (International Journal of Engineering and Technology, 2018)
There are a number of machines available now for floor cleaning. In that many, used for a specific purpose like mopping, vacuum cleaning and combination of both. But all these are operated manually with the help of humans. Nowadays, the technology has developed a lot and a new invention has come to overcome the existing model. Earlier, the moping and vacuum cleaner are combined with a single machine for cleaning the floor. This machine was big and operated manually with human with the continuous movement. But in this project, the movement with the machine was stopped and operated using Wi-Fi signal. With the help of circuit connections, this model was developed in a compact manner for floor cleaning. This floor cleaning machine was designed simply and can be handled very easily by everyone. This helps the people to clean the floor easily in every part of the area by sitting in a place. Here we used Arduino mega 2560 for controlling the working of this machine.